À escuta do vivente: animalidade e biopolítica em Clarice Lispector - Sant Anna Junior, Evandro Ramos de (2023)
This doctoral thesis appreciates that an attentive reading of the relations between human and animal, as expressed in the fictional work of Clarice Lispector, indicates that the space occupied by animal life in such narratives lies beyond the symbolic and representative realms, acting as a political sign that complicates the means by which we relate to the other. In this sense, by considering the theoretical contributions of Marília Librandi and Jean-Luc Nancy, it analyzes how the animal and the human are designated within Lispector’s fictional weaving, with special attention to the notion that, through her work, the Brazilian writer manages a call for a listening exercise that is capable of triggering, on those who are faced with her texts, a legitimate opening towards alterity in its radical form. From the theoretical groundwork of Rosi Braidotti, Maria Cristina Veloso and Juliana Fausto, it examines how the hierarchical distinction of humananimal was established in the western world over the centuries, and the way the Claricean writing questions such a distinction. In addition, with the support of Gabriel Giorgi, Claudete Daflon and Anibal Quijano, it considers to what extent the animality inscribed in the narrative tissue of Clarice Lispector sheds light on a biopolitical and colonial landscape that violates human lives perceived as less-than-human. By exposing that the human-animal distinction also creates the frameworks that are responsible for determining which lives are “killable” and which ones are worthy of being well lived, it highlights, in dialogue with Judith Butler and Jacques Derrida, the fact that the narrative production of Lispector outlines precarity as an element that touches all beings, regardless of species, thereby emphasizing that the exercise of grief and availability to the other, when engaged without hierarchical undertones, configures a gesture that is capable of fracturing the biopolitical dictums maintained on top of a social organization centered in the human figure.